Association Between Bacterial Count and Polymorphonuclear Cells in Uterine Lavage of Postpartum Subclinical Endometritic Cows - Rana, Anchal; Singh, Madhumeet (The Indian Journal of Animal Reproduction, 2022)
This study was conducted to find out the total bacterial count and percentage of polymorphoneutrophils (PMN) cells in uterine lavage samples obtained at a weekly interval from postpartum dairy cows and also to find out the correlation between total bacterial count and PMN cells recovered from the uterus of postpartum dairy cows. Twenty-one postpartum dairy cows were divided into two groups viz. group A (without postpartum complication; n=16) and group B (retained placenta/postpartum metritis; n=5) calving. Cows belonging to the group B were administered antibiotics for 5 days after parturition. Samples for endometrial cytology and total bacterial count were collected aseptically by uterine lavage method at weekly intervals from day 21 to 42 postpartum. Data were statistically analysed by using one-way ANOVA, correlation using Statistical Analysis Software, SAS® 9.2 TS Level version 2M2 for Windows (USA). Based on endometrial cytology, the incidence of sub-clinical endometritis (SCE) recorded was 18.75% in group A and 100% in cows with postpartum complications (Group B). Total bacterial count in the group A animals differed significantly (P<0.05) with the group-B animals. However, the difference between the total bacterial counts in group-A animals and diagnosed negative or positive for SCE did not differ significantly. A highly significant (P<0.05 and P<0.01) correlation was found between bacterial load and PMN cells obtained by uterine lavage technique.